The Leadership Is Given Factors: Fintech Impact in Rural Bank Performance - Tedyono, Rico; Madyan, Muhammad; Harymawan, Iman (RSF Conference Series: Business, Management and Social Sciences, 2023)
The small business enterprise sector (SME) has a significant role in the development of the national economy. However, the existence of small businesses is inseparable from a number of problems they face, namely the problem of capital and the difficulty of access to sources of financing from formal financial institutions, especially banks, and the small opportunity to get business opportunities. Rural Banks have a very important role in overcoming capital problems faced by businesses in Indonesia so researchers are motivated to conduct research on Rural Banks in applying financial technology. The Sources of data in this study come from observations and interviews conducted using semi-structured interviews to obtain the necessary information on whether the directors of Rural banks are able to adapt to fintech. With this research, it will answer how the application of fintech will improve the performance of Rural banks through aspects of individual performance and Rural bank performance itself.